Discharge after coronary artery bypass grafting: A qualitative study highlighting the need for individualised, person-centred care - Melanie Rushton; Michelle Howarth; Heather Iles-Smith (PLoS ONE, 2026)
Background This study explores patient preparedness and support during discharge following coronary artery bypass graft (CABG) surgery. Despite the importance of effective discharge planning, many patients feel unprepared and unsupported, which can hinder recovery and increase readmission risk. Aim To examine patient experiences of the discharge process post-CABG, focusing on education received and perceptions of person-centred discharge planning. Methods A qualitative study using constructivist grounded theory was conducted with eleven participants, interviewed 4–6 weeks post-surgery at a UK Northern NHS hospital. Semi-structured interviews were digitally recorded, transcribed, and analysed using a constant comparative method. Recruitment, data collection, and analysis occurred concurrently. Despite the modest sample size, the study achieved strong information power as the research aim was narrow and clearly focused on exploring the lived experiences of patients who had had a coronary artery bypass graft. This allowed for in-depth engagement with each participant, with relevant experience, enhancing the relevance and the richness of the data. Thematic saturation was observed early in the analysis, indicating that the data sufficiently addressed the research questions. The use of a rigorous analytical approach further ensured that the insights drawn were both meaningful and robust, supporting the adequacy of the sample size. The COREQ checklist guided reporting. Results Four key themes emerged: Patients avoided seeking support or “making a fuss.” Many felt unprepared for discharge. The information booklet was a valuable resource. Lack of post-discharge contact and continuity caused concern. Some participants reported insufficient pre-discharge information and unclear pathways for post-discharge support. The booklet was often the primary source of guidance. The participants’ reluctance to seek support could reflect a pattern of self-management shaped by uncertainty, low confidence, a desire not to burden healthcare professionals or a belief that doctors know best. Yet many felt unprepared for discharge perhaps highlighting gaps in communication and discharge planning. There also seems a reliance on written materials, such as the information booklet. Limited post- discharge contact, created further anxiety, where patients were unsure where to turn for advice. These findings point to the need for clearer, more person‑centred discharge processes. Better communication, improved pre‑discharge education, and clear pathways for follow‑up support could strengthen patient confidence and safety. Although booklets are helpful, they should supplement and not replace ongoing contact and personalised guidance. Ensuring continuity of care and enabling patients to seek help without hesitation is essential for effective person‑centred discharge practice. Conclusion Findings highlight the importance of person-centred approaches in discharge planning. Tailored education and support could improve patient confidence and symptom management during recovery, potentially reducing readmission rates.